Signature Of stiffness transition in electrical behaviour of Se-Te-Sn-Ge glassy alloys. Issue 23 (2nd December 2021) - Pal, Shiv Kumar; Mehta, Neeraj; Dahshan, A.
ABSTRACT: In the family of amorphous semiconductors, non-oxide chalcogenide glasses (ChGs) are in the spotlight because of their widespread applications in various scientific and industrial fields. In this paper, we have studied thermally activated A.C. conduction in multi-component Se-Te-Sn-Ge (STSG) glassy alloys in bulk form at different audio frequencies. The activation energy of A.C. conductivity and other electrical parameters have also been calculated to explore the material's conduction mechanism. The A.C. conductivity σac is found proportional to ω s where ω is the angular frequency. The frequency exponent s is found to decrease with increasing temperature, which is in agreement with the correlation barrier hopping (CBH) model. The variation of the A.C. conduction with temperature and frequency of the glasses has been studied. Their microstructure has also been studied using the XRD characterisation technique to explore their electrical transport properties. XRD patterns confirm the glassy nature of the as-prepared samples. The change in behaviour of various electrical parameters after 2 atomic weight percentages of Ge indicates the occurrence of a stiffness transition followed by a self-organisation of the corner-sharing and the edge-sharing arrangements of the GeSe4 phase.